PEMBUATAN BIOBRIKET DARI LIMBAH DEDAUNAN - Farham HM Saleh; Riffi Restu Hadi; Adiliawan Imam As Shidiq; Sari Ayu Nyimas Genyai; Gita Kencana Pertiwi (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
There were so many leaves waste in our environment. This reseach is conduct to study the possibility of using that waste as a raw material of Bio-briquettes. The leaves that useare mangoes, jackfruits, rambutans, and teak wood powder as comparison. Bio-briquettes were make with and without pyrolysis, for 2 and 5 gram starch. The characteristics test, flame test and water boiling test are conducted with Anglo and Biomassa Stove. The results of the test shows that only moisture content that meet SNI, but the good information that the calories of three type of leaves are more than 4,600 calories/gram, especially the rambutan leaves is 4960 calories/gram. The SNI standar for wood is 5,000 caloris/gram. The flame test results shows that at Biomassa Stove better than at Anglo, and 2 gram starch better than 5 gram. For water boiling test at Angglo is better than at Biomassa Stove, and 2 gram starch better than 5 gram.